Urgensi Pembentukan Peraturan Daerah tentang Perlindungan dan Pengelolaan Hutan Perempuan Teluk Youtefa Kota Jayapura, Papua - Ilham, Ilham; Idris, Usman; Kadir, Akhmad; Tokang, Maspawati; Patmasari, Eka (JURNAL EKOLOGI BIROKRASI, 2023)
This article discusses the urgency of establishing local regulations on the protection and management of women's forests based on traditional wisdom. The type of research used is qualitative with a library approach. Data were obtained from various literature sources relevant to the research topic. Data analysis was carried out through three stages; data reduction, data presentation and verification. Furthermore, the validity of the data was tested using triangulation and discussion techniques. The results of this study show that the mangrove forest area of Youtefa Bay based on customary law principles belongs to women in the local language called "Tonotwiyat". Women's forests are guarded and cared for by women based on traditional wisdom handed down from generation to generation which is a source of local food, a place for social and cultural interaction and even a place for character education for adult women before marriage. The tradition of maintaining and caring for women's forests is now starting to erode along with the destruction of the mangrove ecosystem due to environmental pollution and development activities that are not environmentally friendly. Efforts are being made by the government to rehabilitate mangrove areas that have been converted. As a recommendation, there is a need for regional regulations that are specific to the protection and management of mangrove forests based on traditional wisdom. This is intended so that the mangrove ecosystem remains sustainable, as well as an effort to save and protect the local wisdom of the coastal community of Youtefa Bay as one of the capital of sustainable development.